2013
DOI: 10.1111/iwj.12160
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐benefit of using soft silicone multilayered foam dressings to prevent sacral and heel pressure ulcers in trauma and critically ill patients: a within‐trial analysis of the Border Trial

Abstract: Little is known about the cost-benefit of soft silicone foam dressings in pressure ulcer (PU) prevention among critically ill patients in the emergency department (ED) and intensive care unit (ICU). A randomised controlled trial to assess the efficacy of soft silicone foam dressings in preventing sacral and heel PUs was undertaken among 440 critically ill patients in an acute care hospital. Participants were randomly allocated either to an intervention group with prophylactic dressings applied to the sacrum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 14 publications
1
79
0
3
Order By: Relevance
“…This cost savings estimate related to prevention is also consistent with other cost analysis studies of pressure ulcers. [63][64][65][66] Our robust prevention program, now including the dressing, has yielded a substantial cost savings and has contributed to our sustained pressure ulcer incidence of zero to 0.2 (all stages of HAPUs) in the past 2 years since completion of this trial.…”
Section: Discussionmentioning
confidence: 99%
“…This cost savings estimate related to prevention is also consistent with other cost analysis studies of pressure ulcers. [63][64][65][66] Our robust prevention program, now including the dressing, has yielded a substantial cost savings and has contributed to our sustained pressure ulcer incidence of zero to 0.2 (all stages of HAPUs) in the past 2 years since completion of this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Concerted efforts were made to be more proactive in implementation of prevention strategies, such as encouraging the use of fluidized positioners and use of silicone gel adhesive dressings whenever there were pressure points, depending on the patient's position. Although it is difficult to isolate the effects of individual program components, previous studies 4,11 have shown that application of 5-layer, silicone foam dressings can complement an existing pressure ulcer prevention program. It was our understanding that use of dressings contributed to the reduction in device-related HAPUs.…”
Section: Discussionmentioning
confidence: 99%
“…In a database of 710 626 patients in adult critical care, step-down, medical, surgical, and medical/ surgical units, 3.6% of all patients and 7.9% of those considered at risk had hospital-acquired pressure ulcers (HAPUs; ie, pressure ulcers noted ≥ 24 hours after admission) develop. 2 In acute care settings, the estimated incidence of HAPUs varies widely (eg, from 0.4 to 12% 3 and from 3.3 to 53.4% 4 ).…”
mentioning
confidence: 99%
“…A controlled clinical trial with 440 patients from an emergency service and intensive care unit at a hospital in Australia (11) found that absorbent foam dressing with a silicone border prevents sacral and calcaneus pressure ulcers, and, consequently, resulted in an economic saving for the hospital. In this sense, it is important to consider the evaluation of absorbent foam dressing with a silicone border in comparison with transparent film dressing, which in our study was more cost-effective in preventing sacral pressure ulcer.…”
Section: Resultsmentioning
confidence: 99%